2020
DOI: 10.15832/ankutbd.445671
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Efficacy and Repellency of Trans-Anethole Against Four Stored-Product Insect Pests

Abstract: In this study, it was investigated that repellency and insecticidal efficacy of trans-anethole of botanical origin on major stored product on pests species, namely Sitophilus granarius (L.) (Coleoptera: Curculionidae), Sitophilus oryzae (L.) (Coleoptera: Curculionidae), Tribolium confusum Jacquelin du Val (Coleoptera, Tenebrionidae) and Tribolium castaneum (Herbst) (Coleoptera, Tenebrionidae). Repellency effect was evaluated by choice test in petri dishes, while the mortality effect was examined by exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…A similar repellent effect on T. confusum adults had been observed earlier with Lavandula spica essential oil and its main component linalool [9]. In addition to the repellent effect found in the present study, anethole also showed significant toxicity by fumigation against T. confusum and Sitophilus oryzae adults [28], as well as repellency to two Tribolium and two Sitophilus species [29]. Additionally, caryophyllene has been reported to have a repellent effect on T. castaneum [30].…”
Section: Discussionsupporting
confidence: 89%
“…A similar repellent effect on T. confusum adults had been observed earlier with Lavandula spica essential oil and its main component linalool [9]. In addition to the repellent effect found in the present study, anethole also showed significant toxicity by fumigation against T. confusum and Sitophilus oryzae adults [28], as well as repellency to two Tribolium and two Sitophilus species [29]. Additionally, caryophyllene has been reported to have a repellent effect on T. castaneum [30].…”
Section: Discussionsupporting
confidence: 89%
“…and Petry) could serve as a potential grain protectant against many insect pests 19,20 . Alkan and Erturn 21 reported that trans ‐anethole, with its efficacy in population suppression and its repellency, had strong potential as a bio‐pesticide against stored product insect pests. Trans ‐anethole is found naturally in many plant species of Apiaceae, namely anise, fennel, and star anise.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The star anise fruit is rich in flavonoids, anisole, organic acids, anethole, and other active ingredients, [4] of which (E)-anethole (1-methoxy-4-((E)-propenyl)-benzene) has the highest content. (E)-Anethole, which is the major component in the essential oil of star anise and includes a phenylpropanoid C6-C3 active structural unit, [5] not only can be used as flavor and fragrance, but also shows various biological activities, such as anti-inflammatory, [6] antifungal, [7,8] antitumor, [9] insecticidal, [10] anti-oxidation, [11] etc. So (E)-anethole deserves further investigation in search of more potential bioactive derivatives.…”
Section: Introductionmentioning
confidence: 99%